Design, synthesis, biological evaluation and molecular modeling of N-isobutyl-N-((2-(p-tolyloxymethyl)thiazol-4yl)methyl)benzo[d][1, 3] dioxole-5-carboxamides as selective butyrylcholinesterase inhibitors. (1st April 2022) - Xi, Meiyang; Feng, Chengjie; Du, Kui; Lv, Weiping; Du, Chenxi; Shen, Runpu; Sun, Haopeng
Graphical abstract: Highlights: We discovered the thiazolamide based scaffold as a selective BuChE inhibitor. 33 derivatives were synthesized and assessed for preliminary SAR investigation. The optimal compound 23 showed a competitive manner in a kinetic test. Docking and MD simulation were conducted to further explore the binding mode. 23 showed low toxicity and high blood brain barrier permeability in vitro . Abstract: Butyrylcholinesterase (BuChE) is recently regarded as a biomarker in progressed Alzheimer's disease (AD). Development of selective BuChE inhibitors has attracted a great deal of interest and may be a viable therapeutic strategy for AD. Recently, we reported the N -isobutyl- N -((2-(p-tolyloxymethyl)thiazol-4-yl)methyl)benzo[ d ][1, 3]dioxole-5-carboxamide (1 ) as a selective BuChE inhibitor. Subsequently, 33 analogs were synthesized and assessed by AChE/BuChE activities, indicating an optimal compound 23 . Further kinetic tests suggested a competitive manner. Molecular docking and Molecular dynamics (MD) simulation showed that it interacted with several residues in active site gorge of BuChE, possibly contributing to its selectivity and competitive pattern. Moreover, it showed low cytotoxicity and high blood brain barrier (BBB) permeability. Taken together, 23 was a promising BuChE inhibitor for the treatment of AD.